PLTN Terapung DESAIN KONSEPTUAL PLTN TERAPUNG DI INDONESIA TIMUR: RESPON GERAK TERHADAP BEBAN LINGKUNGAN: Respon Gerak PLTN Terapung di Perairan Pulau Halmahera - Muh. Asyhari Ramadhan; Muh. Hadid Kaharuddin; A. Muh. Ikram; Fuad Mahfud Assidiq (Riset Sains dan Teknologi Kelautan, 2026)
Abstract Eastern Indonesia is characterized by an archipelagic geography with uneven energy distribution, thus requiring alternative energy sources that are reliable, sustainable, and capable of reaching remote areas. One potential solution is the deployment of Floating Nuclear Power Plants (FNPP) in offshore waters around the archipelago. Nuclear energy, with its very low carbon emissions and high electricity generation capacity, is considered a promising option. This study focuses on the conceptual design of a floating nuclear power plant and the motion response of the installation under environmental loads such as ocean waves, wind, and tsunami potential, which are typical in Eastern Indonesia. Oceanographic parameters such as water depth, distance from the island to the FNPP, current velocity, and proximity to the shoreline were analyzed, with Halmahera Island identified as a potential site due to its stable marine conditions, approximately 100 meters in depth, and a distance of less than 30 km from the coast. The site also benefits from proximity to settlements while considering safety, logistics, and potential support for blue economy development. A literature study and simulation using ANSYS software on an Offshore Floating Nuclear Power Plant (OFNP) SPAR-type model demonstrate that an effective mooring system and optimal design are required to maintain long-term stability and operational performance of the FNPP, as well as to ensure reliable electricity distribution to Halmahera Island. In line with SDG 7 (Affordable and Clean Energy) and SDG 9 (Industry, Innovation, and Infrastructure), this design is expected to serve as a strategic recommendation for the development of floating nuclear power plants in Eastern Indonesia. Keywords: Blue economy, Eastern Indonesia, Offshore Floating Nuclear Power Plants (OFNP), Motion response, Platform stability, ANSYS simulation.